Pengaruh Suhu Dan pH Terhadap Bentuk Partikel Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Kulit Telur Itik Melalui Metode Presipitasi - Fadli, Deno Febri; Azis, Yelmida; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (Ca10(PO4)6(OH)2) is the most stable form of calcium phosphate, which is widely used in various medical applications, mainly in orthopedics and dentistry due to it’s similarities with inorganic mineral component of bone and teeth. However, in spite of chemical similarities, mechanical performance of synthetic hydroxyapatite was very poor compared with that of natural bone. It is possible to improve the properties of hydroxyapatite ceramics by controlling important parameters of powder precursors such as particle size, particle shape and agglomeration. In this study, synthesized of hydroxyapatite used PCC and (NH4)2PO4 as raw material by using precipitation method. The PCC was made from duck’s eggshells with carbonation method. The hydroxyapatite obtained by varying the temperature (30oC, 50oC, 70oC) and pH (8, 10, 12), would be sintered in 500 oC and then characterized by using SEM and XRD. Plate-like hydroxyapatite was synthesized at temperature 30oC; pH 10 and temperature 50oC; pH 10, needle-like hydroxyapatite was synthesized at temperature 70oC; pH 10. XRD analysis showed the similarities with standard hydroxyapatite ICDD 01-072-1243. It has been found that the degree of crystallinity had been raised as the temperature and pH increased.Keywords: duck eggshells, hydroxyapatite, particle shape, precipitation